Technical and clinical aspects of cortisol as a biochemical marker of chronic stress - Lee, Do Yup; Kim, Eosu; Choi, Man Ho (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2015)
Stress is now recognized as a universal premorbid factor associated with many risk factors of various chronic diseases. Acute stress may induce an individual's adaptive response to environmental demands. However, chronic, excessive stress causes cumulative negative impacts on health outcomes through "allostatic load". Thus, monitoring the quantified levels of long-term stress mediators would provide a timely opportunity for prevention or earlier intervention of stress-related chronic illnesses. Although either acute or chronic stress could be quantified through measurement of changes in physiological parameters such as heart rate, blood pressure, and levels of various metabolic hormones, it is still elusive to interpret whether the changes in circulating levels of stress mediators such as cortisol can reflect the acute, chronic, or diurnal variations. Both serum and salivary cortisol levels reveal acute changes at a single point in time, but the overall long-term systemic cortisol exposure is difficult to evaluate due to circadian variations and its protein-binding capacity. Scalp hair has a fairy predictable growth rate of approximately 1 cm/month, and the most 1 cm segment approximates the last month's cortisol production as the mean value. The analysis of cortisol in hair is a highly promising technique for the retrospective assessment of chronic stress.
Keywords: URINARY FREE CORTISOL; HAIR CORTISOL; SCALP HAIR; METABOLOMICS; CORTICOSTEROIDS; DIAGNOSIS; BIOMARKER; DISORDER; PATTERN; OBESITY